Enhanced introduction of extra-framework metal into aluminosilicate zeolite

A simplified single-step process for metal incorporation into aluminum-containing zeolites addresses inefficiencies in existing methods by directly forming and using the metal-containing zeolite mixture, enhancing efficiency and reducing costs.

JP2025016480AActive Publication Date: 2025-02-04JOHNSON MATTHEY PLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024174320
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-11-30
Filing Date
2024-10-03
Publication Date
2025-02-04
Estimated Expiration
2039-11-29

AI Technical Summary

Technical Problem

Existing methods for introducing metals into aluminum-containing zeolites are inefficient and costly, requiring multiple processing steps and high operational costs, leading to unnecessary waste and energy consumption.

Method used

A single-step process for incorporating metals into aluminum-containing zeolites by forming a mixture with metal compounds without ammonia or ammonium salts, followed by a reaction and direct use of the resulting mixture without separation, which simplifies the process and reduces energy and material usage.

Benefits of technology

This method enhances metal incorporation efficiency, reduces energy and material costs, and eliminates the need for additional processing steps, resulting in improved throughput and cost savings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016480000001_ABST
    Figure 2025016480000001_ABST
Patent Text Reader

Abstract

To provide a simplified preparation process of a metal-containing aluminosilicate zeolite.SOLUTION: A process involves the steps of: (a) forming a reactant mixture A containing (i) an aqueous slurry of an aluminosilicate zeolite in the H+-form and (ii) a metal-containing compound or free metal, where the metal-containing compound or free metal contains copper carbonate and / or copper hydroxide, and where the mixture A does not contain ammonia, ammonium hydroxide or an ammonium salt; and (b) reacting the metal-containing compound or free metal with the aluminosilicate zeolite in the H+-form in the reactant mixture A to form a product mixture B containing an extra-framework metal-containing aluminosilicate zeolite. The metal includes one or more of Cu, Mn, Ni and Pd. The step of reacting the metal-containing compound or free metal with the aluminosilicate zeolite in the H+-form is performed in single exchange. After forming the mixture B, the extra-framework metal-containing aluminosilicate zeolite is not separated from the mixture after the reaction.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention converts metal ions to H in a single step. + The present invention relates to a process for producing an extraframework metal-containing aluminosilicate zeolite by ion-exchanging aluminosilicate zeolite of the type described above into a zeolite of the type described above, and the resulting reaction mixture can be used to form a washcoat. This process differs from conventional ion-exchange processes in that the reaction mixture is separated from the formed metal-containing aluminosilicate, and the metal-containing aluminosilicate is generally washed with water in repeated steps that remove impurities from the metal-containing aluminosilicate. [Background technology]

[0002] Aluminosilicate zeolites are crystalline aluminosilicate materials that have fairly uniform pore sizes, generally ranging from about 3 to 10 Angstroms in diameter, depending on the type of zeolite, the location of the cations, the type of cations, and the number of cations contained in the zeolite.

[0003] The use of synthetic zeolites in promoting certain reactions, such as the selective catalytic reduction (SCR) of nitrogen oxides with reducing agents such as ammonia, urea and / or hydrocarbons in the presence of oxygen, is well known in the art.

[0004] The process of synthesizing zeolites may vary depending on the framework structure of the zeolite. Zeolites are usually synthesized using a structure directing agent (also called a template or organic template) along with sources of silica and alumina. The structure directing agent can be an organic compound, such as tetraethylammonium hydroxide (TEAOH), or an inorganic cation, such as Na + Or K + During crystallization, the tetrahedral silica-alumina units are organized around structure directing agents (SDAs) to form the desired framework, which are often contained within the pore structure of the zeolite crystal.

[0005] It has been found that the introduction of extra-framework metals into aluminosilicate zeolites can improve the catalytic activity of the aluminosilicate zeolites. Researchers have described various methods for introducing various metals into a number of molecular sieves.

[0006] Dedecek et al. (Microporous and Mesoporous Materials 32 (1999) 63-74) reported that Na + , Ca 2+ , Cs + , and Ba 2+ Direct exchange into type chabazite was investigated. A single exchange process produced materials with Cu / Al ratios ranging from 0.01 to 0.28. Two ion exchanges produced materials with Cu / Al ratios of 0.34, 0.38, and 0.32.

[0007] In WO 2008 / 077590, iron, copper and / or silver are added to Na zeolites having the MFI or BEA structure. + A process of direct metal exchange into the mould is described, where the metal exchange is carried out by suspending the zeolite in an aqueous solution containing the metal ions and ammonium ions.

[0008] In WO 2008 / 106519 (U.S. Patent No. 7,601,622), copper sulfate or copper acetate and NH4 + discloses catalysts comprising zeolites having a CHA crystal structure prepared via copper exchanging type CHA. The process of ion exchange, filtering, washing, and drying was performed at least twice (repeated at least once). In some examples, multiple ion exchange, filtering, washing, and drying steps were used, with these steps being performed up to five times. In some examples, coating slurries comprising calcined CuCHA catalysts were treated with additional copper sulfate to increase the total concentration of CuO. In one example, a CuCHA catalyst containing 1.94% CuO was prepared by a single ion exchange, but details of the exchange were not provided.

[0009] In WO 2008 / 132452, various small pore NH4+ It is disclosed that zeolites (SAPO-34, SSZ-13, Sigma-1, ZSM-34, ZSM-5) and Beta (a large pore zeolite) can be ion-exchanged with transition metals. It is disclosed that this procedure can be repeated to achieve a desired metal loading higher than that obtainable by a single ion exchange. According to the examples, multiple aqueous ion exchanges may be required to achieve the desired loading of 3 wt. % Cu.

[0010] In US Patent No. 2011 / 0165052, copper was mixed with Na + They disclose a method for preparing CuCHA by ion exchange into CHA in the NH4 or NH4 form.

[0011] US 2017 / 0095804 discloses a method for preparing metal-exchanged zeolites by providing a dry mixture of (a) one or more microporous zeotype materials exhibiting ion exchange capacity and (b) one or more metal compounds, and heating the mixture to a temperature below 300° C. in a gas atmosphere containing ammonia for a time sufficient to initiate and carry out solid-state ion exchange of ions of the metal compounds with ions of the zeolitic material. Also disclosed are advantages of using solid-state ion exchange over conventional methods of contacting a zeolite with a solution of the desired metal ions.

[0012] No. 8,795,626 relates to chabazite-type zeolites having copper and alkaline earth metals supported thereon. In one example, conventional ion exchange is used to convert Cu to H + After the reaction, the solid is separated from the liquid, washed and dried, and then the alkaline earth metal is exchanged for CuCHA.

[0013] Unfortunately, achieving the desired metal loading can involve inefficient and wasteful procedures. There is a continuing desire to simplify the process for preparing metal-containing aluminosilicates because the process involves many processing steps that add capital and operational costs to the manufacturing process. Summary of the Invention

[0014] The process for preparing extraframework metal-containing aluminosilicate zeolites is as follows: (a)(i)H + forming a reaction mixture A comprising an aqueous slurry of an aluminosilicate zeolite of type I; and (ii) a metal-containing compound or free metal, the mixture being free of ammonia, ammonium hydroxide, or ammonium salts; and removing the metal or free metal in the metal-containing compound by removing H from the reaction mixture A. + type aluminosilicate zeolite to form a product mixture B comprising an extraframework metal-containing aluminosilicate zeolite, + wherein reacting with an aluminosilicate zeolite of type I is performed in a single exchange, and after forming product mixture B, the extraframework metal-containing aluminosilicate zeolite is not separated from product mixture B.

[0015] A process for preparing a washcoat comprising an extraframework metal-containing aluminosilicate zeolite comprises: (a) providing a product mixture B comprising an extraframework metal-containing aluminosilicate zeolite according to a process described herein; and (b) combining product mixture B, i.e., the reaction mixture comprising the extraframework metal-containing aluminosilicate zeolite, with a binder, a rheology modifier, or a mixture of binders and rheology modifiers to form a washcoat mixture C.

[0016] The methods described herein have several advantages over the current state of the art in terms of efficiency, minimization of waste streams, and reduction in required steps, which can increase the throughput of articles manufactured using the extraframework metal-containing aluminosilicate zeolite while reducing energy usage. The product mixture B containing the metal incorporated in the aluminosilicate zeolite can be used directly in forming a washcoat without the need to (a) remove water and undesired reaction products from the product mixture B, (b) wash or further treat the extraframework metal-containing aluminosilicate zeolite, and / or (c) calcinate the metal incorporated in the aluminosilicate zeolite.

[0017] This simplifies the overall process, allowing both increased productivity and energy and material savings, since there is no need to wash the reaction mixture to remove metals not incorporated in the aluminosilicate zeolite, and no need to remove water. It also eliminates the need for two calcination steps, one when making the extraframework metal-containing aluminosilicate zeolite and one after the washcoat is applied onto the substrate. The method described herein allows for the elimination of the calcination step when making the extraframework metal-containing aluminosilicate zeolite. This allows for capital savings in separate drying and calcination equipment, and working capital savings by reducing working inventory. [Brief description of the drawings]

[0018] [Figure 1] 1 shows steady-state NOx conversion and N2O concentration based on samples prepared by the methods described herein after mild hydrothermal aging (620° C. / 100 h / 10% H2O). [Diagram 2] 1 shows steady-state NOx conversion based on samples prepared by the methods described herein after moderate hydrothermal aging (750° C. / 80 h / 10% HO). [Diagram 3]1 shows steady-state NOx conversion based on a sample prepared by the methods described herein after severe hydrothermal aging (900° C. / 4 h / 4.5% HO). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] As used herein, the singular forms "a," "an," and "the" include plural referents unless the content clearly dictates otherwise. Thus, for example, reference to "a catalyst" includes a mixture of two or more catalysts, and the like.

[0020] The term "about" means approximately and refers to a range, optionally of ±25%, preferably ±10%, more preferably ±5%, or most preferably ±1% of the value with which the term is associated.

[0021] Where a range or ranges for various numerical elements are specified, the range or ranges are inclusive of the values ​​unless otherwise specified.

[0022] As used herein, the term "metal" refers to copper, iron, manganese, nickel and / or palladium exchanged onto or located on the aluminosilicate zeolite. As used herein, the term "metal-containing compound or free metal" refers to the metal, oxide or free metal that is the cation in a salt of the metal. When the metal is present as a cation, the metal may be present in solution in the form of a salt that includes the metal as the cation along with the anion.

[0023] The term “H + "Type" aluminosilicate zeolite refers to an aluminosilicate zeolite having a framework charge substantially balanced by protons. In this type, the aluminosilicate zeolite generally has H + and a mixture of alkali and / or alkaline earth cations. + Aluminosilicate zeolites of the type H +In the form, the H may be ≧90%, ≧95%, ≧96%, ≧97%, ≧98%, or ≧99%. + The amount of type aluminosilicate zeolite may vary depending on the particular aluminosilicate zeolite batch and the method used to form the aluminosilicate zeolite.

[0024] The term "extraframework metal-containing aluminosilicate zeolite" refers to an aluminosilicate zeolite in which the metal is on the surface and / or inside the cages and / or pores of the aluminosilicate zeolite. It does not refer to an aluminosilicate in which the metal is in the aluminosilicate framework.

[0025] Pores are openings that extend from one side of the crystal to the other, but are not linear. Cages are polyhedral pores whose windows, or faces of the polyhedral pores, are too narrow to allow molecules larger than water to enter. This means that the maximum size of a cage window is a six-membered ring.

[0026] When the metal is a cation of a salt, the term "react" refers to the ion exchange of the metal into the zeolite. When the metal is a metal oxide or free metal, the term "react" refers to the transfer of the metal oxide or free metal onto and / or into the zeolite.

[0027] When the metal is a cation of a salt, the term "product mixture C" refers to the mixture formed after metal exchange with the aluminosilicate zeolite occurs to form an "extraframework metal-containing aluminosilicate zeolite." The metal exchange can be an ion exchange. The reaction mixture includes the "extraframework metal-containing aluminosilicate zeolite," any reaction products present in the mixture, and water. When the metal is a free metal or an oxide of the metal, the term "product mixture C" refers to the mixture formed after the metal or oxide of the metal migrates to extraframework sites in the aluminosilicate zeolite.

[0028] The term "calcining" or "calcination" means heating a material in air, oxygen, or an inert atmosphere. This definition is consistent with the IUPAC definition of calcination. (IUPAC. Compendium of Chemical Terminology, 2nd ed. (the "Gold Book"). Prepared by A.D. McNaught and A. Wilkinson. Blackwell Scientific Publications, Oxford (1997). XML online revision: http: / / goldbook.iupac.org (2006-), prepared by M. Nic, J. Jirat, B. Kosata, updated by A. Jenkins. ISBN 0-9678550-9-8. doi:10.1351 / goldbook.) Calcination is performed to decompose metal salts, promote exchange of metal ions in the catalyst, and to adhere the catalyst to the substrate. The temperature used for calcination varies depending on the components in the material being calcined, and is generally from about 400° C. to about 900° C. for about 0.25 to 8 hours. In some cases, calcination can be carried out at temperatures up to about 1200° C. For applications involving the processes described herein, calcination is generally carried out at temperatures from about 400° C. to about 700° C. for about 0.25 to 8 hours, preferably from about 400° C. to about 650° C. for about 0.25 to 4 hours.

[0029] The term "washcoat" refers to a carrier of catalytic material used to disperse the material over the majority of the surface on a substrate. The catalytic material is suspended in the washcoat prior to application of the washcoat to the substrate.

[0030] The term "comprising" is synonymous with "including," "containing," or "characterized by," and is inclusive or open-ended and does not exclude additional, unrecited elements or method steps.

[0031] As used herein, the term "consisting essentially of" limits the scope of a feature to include the specified materials, steps, and any other materials or steps, e.g., trace impurities, that do not substantially affect the basic properties of the feature. The phrase "consisting essentially of" encompasses the phrase "consisting of."

[0032] The term "consisting of" excludes any element, step, or ingredient not specified in the claim.

[0033] Described herein is a process for preparing an extraframework metal-containing aluminosilicate zeolite. The process for producing the extraframework metal-containing aluminosilicate zeolite described herein can be carried out using either a batch tank or a continuous process production. The extraframework metal-containing aluminosilicate zeolite obtained or obtainable by the process of the present invention can be processed and used as described in the literature for other extraframework metal-containing aluminosilicate zeolites. The as-prepared extraframework metal-containing aluminosilicate zeolite can also be directly incorporated into a washcoat as part of the process of forming the extraframework metal-containing aluminosilicate zeolite and then forming the washcoat which is applied to a substrate.

[0034] 1. A process for incorporating metals into extra-framework sites in aluminosilicate zeolites The process for preparing an extraframework metal-containing aluminosilicate zeolite comprises: (a)(i)H + forming a reaction mixture A comprising an aqueous slurry of an aluminosilicate zeolite of type A; and (ii) a metal-containing compound or free metal, wherein the mixture does not contain ammonia, ammonium hydroxide, or ammonium salts; (b) The metal is added to H in reaction mixture A. + and reacting said aluminosilicate zeolite of type 1 with said aluminosilicate zeolite of type 2 to form product mixture B, i.e., a reaction mixture comprising an extraframework metal-containing aluminosilicate zeolite; The metal includes one or more of copper, iron, manganese, nickel, and palladium, and the metal is H + The step of reacting with an aluminosilicate zeolite of type I is carried out in a single exchange, and after forming product mixture B, the extraframework metal-containing aluminosilicate zeolite is not separated from product mixture B.

[0035] Process (a) (i)H + and (ii) a metal-containing compound or free metal, wherein the mixture does not contain ammonia, ammonium hydroxide, or ammonium salts.

[0036] The term aluminosilicate zeolite as used herein includes aluminosilicate zeolites having any one of the framework structures listed in the database of zeolite structures published by the International Zeolite Association (IZA). Zeolites have a three-dimensional framework of interconnected tetrahedrons containing aluminum, silicon, and oxygen atoms, with all four oxygen atoms located at the corners of each tetrahedron being shared with adjacent tetrahedral crystals. The non-oxygen atoms within the tetrahedrons are referred to as T-atoms.

[0037] The aluminosilicate zeolites may be small pore, medium pore, or large pore aluminosilicate zeolites, or combinations thereof. Small pore aluminosilicate zeolites typically have pores defined by rings of eight or fewer T atoms and have an average pore size of less than about 0.5 nm (5 Å). Medium pore aluminosilicate zeolites typically have pores defined by rings of ten T atoms and have an average pore size of about 0.5-0.6 nm (5-6 Å), whereas large pore materials have pores defined by rings of twelve or more T atoms and pore sizes greater than 0.6 nm (6 Å).

[0038] The small pore aluminosilicate zeolite may be selected from the group of framework types consisting of ACO, AEI, AEN, AFN, AFT, AFX, ANA, APC, APD, ATT, CDO, CHA, DDR, DFT, EAB, EDI, EPI, ERI, GIS, GOO, IHW, ITE, ITW, KFI, LEV, LTA, MER, MON, NSI, OWE, PAU, PHI, RHO, RTH, SAT, SAV, SFW, SIV, THO, TSC, UEI, UFI, VNI, YUG and ZON, and mixtures thereof and / or intergrowth. Preferably, the small pore aluminosilicate zeolite is selected from the group of framework types consisting of AEI, AFT, AFX, CHA, DDR, ERI, KFI, LEV, LTA, SFW and RHO.

[0039] The medium pore aluminosilicate zeolite may be selected from the group of framework types consisting of AEL, AFO, AHT, BOF, BOZ, CGF, CGS, CHI, DAC, EUO, FER, HEU, IMF, ITH, ITR, JRY, JSR, JST, LAU, LOV, MEL, MFI, MFS, MRE, MTT, MVY, MWW, NAB, NAT, NES, OBW, PAR, PCR, PON, PUN, RRO, RSN, SFF, SFG, STF, STI, STT, STW, SVR, SZR, TER, TON, TUN, UOS, VSV, WEI and WEN, and mixtures thereof and / or intergrowth. Preferably, the medium pore aluminosilicate zeolite is selected from the group of framework types consisting of FER, MEL, MFI, STI and STT.

[0040] The large pore aluminosilicate zeolite may be selected from the group of framework types consisting of AFI, AFR, AFS, AFY, ASV, ATO, ATS, BEA, BEC, BOG, BPH, BSV, CAN, CON, CZP, DFO, EMT, EON, EZT, FAU, GME, GON, IFR, ISV, ITG, IWR, IWS, IWV, IWW, JSR, LTF, LTL, MAZ, MEI, MOR, MOZ, MSE, MTW, NPO, OFF, OKO, OSI, RON, RWY, SAF, SAO, SBE, SBS, SBT, SEW, SFE, SFO, SFS, SFV, SOF, SOS, STO, SSF, SSY, USI, UWY, and VET, and mixtures thereof and / or intergrowth. Preferably, the large pore molecular sieve is selected from the group of framework types consisting of AFI, BEA, GME, MAZ, MOR and OFF.

[0041] The aluminosilicate zeolite is preferably AEI, AFT, AFX, BEA * , CHA, DDR, ERI, FAU, FER, GME, HEU, ITE, KFI, LEV, LTA, MFI, MWW, RHO, RTH, SFW, * The skeletal types include those selected from the group consisting of SFV, STT, SZR, and UFI, and intergrowths and mixtures thereof.

[0042] The aluminosilicate zeolite may have a silica / alumina molar ratio (SAR), defined as SiO2 / Al2O3, of 5-50, preferably 8-40, more preferably 10-35, and even more preferably 13-25.

[0043] The aluminosilicate zeolite can have the same particle size distribution as the desired particle size distribution of the formed extra-framework metal-containing aluminosilicate zeolite. Alternatively, the aluminosilicate zeolite can have a particle size distribution that can be processed by jet milling, wet milling, steam-assisted jet milling, or the like, so that the metal-containing aluminosilicate zeolite has the desired particle size distribution. Wet milling can be performed in a recirculating chamber mill or a basket-type immersion mill. Both wet mills use beads as an attrition medium. Jet milling utilizes high-velocity jets of compressed air to collide particles with each other, causing attrition.

[0044] The aluminosilicate zeolite may be treated prior to use in step (a) to change one or more of the properties of the aluminosilicate zeolite. For example, the treatment may change the particle size or particle size distribution of the aluminosilicate zeolite. The acidity of the aluminosilicate zeolite may be changed by washing the aluminosilicate zeolite with, for example, acid or EDTA. The aluminosilicate zeolite may be subjected to other forms of dealumination, including hydrothermal treatment.

[0045] H + Aluminosilicate zeolites of the type In step (a), H + Applicants have discovered that aluminosilicate zeolites of the type H + It has been discovered that the use of an aluminosilicate zeolite of type NH3 allows the use of a single extra-framework metal exchanger and achieves higher levels of metal uptake than the use of an aluminosilicate zeolite of type NH3, as shown in Examples 1 and 2 below.

[0046] Reaction mixture A is 5% to 50%, preferably 10% to 45%, more preferably 20% to 45%, H + Reaction mixture A may comprise an aluminosilicate zeolite of the type A. Reaction mixture A may be a slurry or suspension, preferably a slurry.

[0047] metal The metals may include one or more of copper, iron, manganese, nickel and palladium, preferably one or more of copper, manganese, nickel and palladium.

[0048] The metals may include one or more of copper, manganese, nickel, and palladium in combination with iron.

[0049] The amount of metal supported in the extraframework metal-containing aluminosilicate zeolite can be 0.1% by weight to 10% by weight, preferably 0.1% by weight to 7% by weight, and more preferably 0.1% by weight to 5% by weight, based on the amount of the aluminosilicate zeolite.

[0050] Metal salts Step (a) may use one or more salts of a metal, the salt of which must contain a cation and an anion of the metal.

[0051] Various salts of metals, or mixtures of salts, can be used. Preferably, the salts of the metals do not complex with other materials during metal exchange. Preferably, at least one of the salts of the metals is soluble in acidic aqueous solutions (pH≦5). A combination of soluble and non-acidic water-soluble (pH≧7) salts of the metals can be used. The salts of the metals preferably include one or more of the following anions: acetate, bromide, carbonate, chloride, citrate, fluoride, formate, hydroxide, iodide, nitrate, oxalate, phosphate and sulfate, or combinations thereof.

[0052] The one or more salts of a metal can include two salts, and the anions of these salts can be selected from acetate, formate, and hydroxide.

[0053] The metal salt may be soluble in water or may be a physical mixture of the metal salt, such as a slurry or suspension.

[0054] Metal concentration in reaction mixture A The metal-containing compound or free metal may be present in a solution, slurry or suspension with a concentration of metal that achieves the desired loading of the metal in the aluminosilicate zeolite with a single ion exchange. If the metal-containing compound is soluble in water, the desired loading may be based on the absorption rate of the metal, determined by the difference between the concentration of the metal in a supernatant sample from product mixture B, i.e., the reaction mixture after the exchange reaction has occurred, and the concentration of the metal in a supernatant sample from reaction mixture A before the reaction has occurred. A supernatant sample can be obtained for analysis by centrifuging a portion of reaction mixture A and product mixture B to separate the solids from the liquid. The difference in the amount of metal in reaction mixture A and product mixture B corresponds to the amount of metal exchanged into the extra-framework sites of the zeolite. If the metal is free metal or in the form of a metal-containing compound that is not soluble in water but is present in a slurry or suspension, samples of reaction mixture A and product mixture B may need to be analyzed in a manner that solubilizes the metal but does not remove the metal from the extra-framework sites of the zeolite.

[0055] The metal-containing compound may be in solution, suspension, or slurry depending on the water solubility and concentration of the metal-containing compound. The concentration of the metal should be at a level that achieves the desired loading of the metal on the aluminosilicate zeolite in a single step. The concentration of the metal in the solution may vary over a wide range depending on the solubility of the metal-containing compound in water, the presence of other water-soluble materials, and the concentration of extraframework metal-containing aluminosilicate zeolite required in the washcoat mixture C (used as a washcoat or to form a washcoat). The concentration of the metal-containing compound in water at the temperature of formation of reaction mixture A or at the temperature of reaction to form product mixture B, i.e., reaction solution, may range from 0.1 to 2.5 molar, preferably 0.5 to 2 molar, more preferably 0.1 to 1 molar, and even more preferably 0.2 to 0.5 molar.

[0056] The metal-containing compound or metal may be in solution, suspension, or slurry depending on the water solubility and concentration of the metal-containing compound or metal. The concentration of the metal should be at a level that achieves the desired loading of the metal on the aluminosilicate zeolite in a single step. The concentration of the metal in the solution may vary over a wide range depending on the solubility of the metal-containing compound in water, the presence of other water-soluble materials, and the concentration of extraframework metal-containing aluminosilicate zeolite required in the washcoat mixture C (used as a washcoat or to form a washcoat). The concentration of the metal-containing compound or metal in reaction mixture A at the temperature of formation of reaction mixture A or at the temperature of reaction to form product mixture B, i.e., reaction solution, may range from 0.01 to 2.5 molar, preferably 0.05 to 2 molar, more preferably 0.05 to 1 molar, and even more preferably 0.075 to 0.5 molar.

[0057] Step (a) requires that reaction mixture A does not contain ammonia, ammonium hydroxide, or ammonium salts. By using ammonia, ammonium hydroxide, or ammonium salts, ammonium complexes with the metal can be formed. For some metals, the complexes can increase the metal concentration in solution. If the pore size of the aluminosilicate zeolite is large enough, the exchange of the metal can be improved. However, for small pore aluminosilicate zeolites, the large radius of the complex can hinder the exchange. If the metal complex is too large, the concentration of the metal in solution increases. If the formation of the complex is more thermodynamically stable, the concentration of the metal in solution increases.

[0058] This can also be viewed as a matter of back exchange and competition between ammonium and the desired metal cation. The presence of the ammonia complex can vary the amount of metal exchanged into the aluminosilicate zeolite.

[0059] In the first part of the process, whether batch or continuous, the aluminosilicate zeolite is dispersed in or mixed with a solution, slurry or suspension of metal-containing compound or free metal with water.

[0060] In a batch process, the aluminosilicate zeolite, preferably as a dry powder / crystals or slurry, can be dispersed or mixed with a solution, slurry or suspension containing the metal-containing compound or free metal.

[0061] In a continuous process, this dispersion or mixing can be done using an in-line continuous mixing system. Examples of such mixers include Silverson in-line LS series mixers, Admix Fastfeed in-line mixers, Ystral Conti TDS mixers, IKA MHD 2000 in-line mixers, and Arde Barinco Dispershear. Preferably, the metal-containing compound is in a solution that can be precisely injected into the mixer, preferably using a rotor stator pump, and the zeolite powder can be precisely injected into the mixer, preferably using a loss-in-weight powder feeder system. This ensures that the solids concentration and metal ion concentration of the output slurry from the mixer are controlled. If the salt is a slurry or suspension, it can be precisely injected into the mixer, preferably using a rotor stator pump, and the zeolite powder can be precisely injected into the mixer, preferably using a loss-in-weight powder feeder system. This ensures that the (a) solids concentration and (b) metal ion concentration of the output slurry from the mixer are controlled.

[0062] H + A mixture is formed of an aluminosilicate zeolite of the type and a solution, slurry or suspension of either a metal-containing compound or free metal of the metal to be incorporated into the aluminosilicate zeolite.

[0063] H +The type aluminosilicate zeolite, the metal-containing compound or free metal, and the water may be added together in any order. + The type aluminosilicate zeolite can be added as a powder or a mixture with water, as a slurry or suspension, to a solution / mixture, preferably an aqueous solution / mixture of a salt of the metal, of a metal-containing compound or of the free metal or a combination.

[0064] The aqueous solution, slurry or suspension of the metal-containing compound or free metal may be at a temperature between 10° C. and 90° C. at which the transmetallation reaction is carried out.

[0065] Alternatively, a solution, slurry or suspension, preferably an aqueous solution, of metal-containing compounds or free metals can be dissolved in H + Type aluminosilicate zeolite or solid H + Depending on the metal-containing compound or free metal and the zeolite, the solution, slurry or suspension of the metal-containing compound or free metal can be added to a mixture of the metal-containing compound and the free metal. After cooling to about 10° C. below room temperature (about 30° C.), at room temperature (about 30° C.), or heating to a temperature of from room temperature (about 30° C.) to about 90° C., preferably from about 50 to about 75° C., and even more preferably from about 55 to about 70° C., the solution, slurry or suspension of the metal-containing compound or free metal can be added to a mixture of the metal-containing compound and the free metal. + The type aluminosilicate zeolite can be added to a solution, slurry or suspension of the metal-containing compound or free metal, or the solution, slurry or suspension of the metal-containing compound or free metal can be heated to 1000° C. + It can be added to aluminosilicate zeolites.

[0066] Reaction mixture A has a pH that depends on the concentrations of the aluminosilicate zeolite, the metal-containing compound or free metal, and the aluminosilicate zeolite and the metal-containing compound or free metal.

[0067] The step of forming reaction mixture A may further include adjusting the pH of reaction mixture A by adding a base. The base is an inorganic base, preferably a metal hydroxide, or an organic base, preferably an alkyl ammonia hydroxide, where the alkyl ammonia hydroxide contains from 4 to 16 carbon atoms.

[0068] The pH of reaction mixture A can be adjusted to be more basic to increase the metal loading on the zeolite in the metal exchange in step b). The step of adjusting the pH of reaction mixture A can include providing an amount of base such that the concentration of hydroxide ions in the solution is equal to or greater than the concentration of metal in the solution.

[0069] The step of adjusting the pH of reaction mixture A may include adding a sufficient amount of base to remove the amount of free metal in solution to less than 10%, preferably less than 5%, and more preferably less than 1% of the total metal.

[0070] Step (b) Metal is reacted with H in reaction mixture A + type aluminosilicate zeolite to form product mixture B which comprises an extraframework metal-containing aluminosilicate zeolite.

[0071] The second part of the process involves incorporating metals into the aluminosilicate zeolite using ion exchange reactions to form extra-framework metal-containing aluminosilicate zeolites.

[0072] The metal is added to reaction mixture A. + The step of reacting reaction mixture A with an aluminosilicate zeolite of type A to form product mixture B comprising an extraframework metal-containing aluminosilicate zeolite comprises mixing reaction mixture A at a temperature and for a time sufficient for the reaction to obtain a desired metal loading on the aluminosilicate zeolite.

[0073] mixture The reaction mixture A, a slurry or suspension, can be mixed appropriately to form a product mixture B that has good mixing to prevent solids settling. Those skilled in the art will be aware of the equipment and techniques that can be used to obtain such mixing.

[0074] Reaction temperature The step of reacting reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite may include cooling or heating the reaction mixture to a temperature of 10° C. to 90° C., preferably 20° C. to 85° C., more preferably 25° C. to 75° C., and most preferably 30° C. to 75° C. If the metal-containing compound in reaction mixture A comprises copper acetate, reaction mixture A should be heated to a temperature of 40° C. to 85° C., more preferably 55° C. to 75° C.

[0075] The step of reacting reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite can include mixing reaction mixture A at a temperature that does not employ heating, such as ambient temperature. In some circumstances, the reaction can be carried out at a temperature that requires cooling, such as 10-12° C. The step of reacting reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite can be carried out at ambient temperature or at a temperature that requires cooling.

[0076] Time for metal exchange or reaction The length of time sufficient to form a mixture comprising a metal-containing aluminosilicate zeolite depends on one or more of the aluminosilicate zeolite, the SAR of the aluminosilicate zeolite, the type of aluminosilicate zeolite, the particle size of the aluminosilicate zeolite, the desired metal loading, the metal salt, the temperature to which reaction mixture A is heated, and the concentrations of the reactants.

[0077] The reaction time for exchange of metal to extraframework sites in the aluminosilicate zeolite during contact of the aluminosilicate zeolite with a solution, slurry, or suspension of a metal-containing compound or free metal can be from about 1 minute to about 24 hours, preferably from about 5 minutes to about 18 hours, more preferably from about 15 minutes to about 12 hours, from about 10 minutes to about 5 hours, from about 10 minutes to about 3 hours, or from about 10 minutes to about 1 hour.

[0078] pH: Use of basic additives The pH of reaction mixture A may be in the range of about 4 to about 7, preferably in the range of about 5 to about 7, and even more preferably in the range of about 5 to about 6.

[0079] Depending on the starting materials used, it may be necessary to adjust the pH of the slurry or suspension so that the pH of reaction mixture A has the above-mentioned value. The pH can be adjusted to the above-mentioned value using a base, which is an inorganic base, preferably a metal hydroxide, or an organic base, preferably an alkyl ammonia hydroxide, which contains 4 to 16 carbon atoms. Preferably, the base is an alkyl ammonium hydroxide.

[0080] Percentage of absorption The percent uptake is a measure of the amount of metal transferred from the metal-containing compound or free metal to the aluminosilicate zeolite as extra-framework metal. The percent uptake is defined as moles of metal in or on the aluminosilicate zeolite / moles of metal in the starting solution x 100. The percent uptake is the total amount of metal exchanged into and adsorbed onto the aluminosilicate zeolite. The percent uptake can range from about 80% to about 98%, depending on the source of aluminosilicate zeolite used, the reaction temperature, and the reaction time. The percent metal uptake can be at least about 80%, preferably at least about 85%, more preferably at least about 90%, and most preferably at least about 92%.

[0081] Cooling of product mixture B If the reaction is carried out at room temperature (maximum 40° C.), cooling of the product mixture B after metal exchange is not required.

[0082] If the reaction is carried out at a temperature above room temperature (above 40° C.), the product mixture B must be cooled to room temperature (up to 40° C.) before the mixture of extraframework metal-containing aluminosilicate zeolites is used to produce a washcoat or is further processed for other uses.

[0083] In a batch process, reaction mixture A is mixed at a temperature without the use of heat or as described above until the desired amount of metal uptake by the zeolite is reached.

[0084] In a continuous process, the output slurry from the first part of the continuous process can be continuously fed into a thermally controlled mixer reactor system to carry out the ion exchange reaction. Typical mixer reactors that can be used for this are tubular reactors, continuous stirred flow reactors, or baffle reactors, such as vibrating baffle reactors, spinning disk reactors, or spinning cone reactors. These reactors can have different types of mixer internals, selected and optimized according to the mixing action required here. Typically, a thermal control system in a desired length of piping containing static mixing elements can be used for operation, provided that the slurry has a residence time in the reactor to ensure that the ion exchange reaction is completed, which can be confirmed by analysis. The reaction mixture A, i.e. the output slurry from the first part of the continuous process, can be pumped through the piping at a controlled and desired rate to complete the reaction within the length of the piping. The static mixing elements in the piping ensure good mixing of the slurry and prevent settling of the zeolite and any other non-soluble components. The outside of the piping can be temperature controlled by an external heating system to ensure sufficient heat transfer throughout the piping to ensure that the slurry in the reactor has the set temperature required for the desired ion exchange. At the ends of the piping, the slurry can be cooled by cooling the exterior surface of the piping.

[0085] If product mixture B (containing the extraframework metal-containing aluminosilicate zeolite) was heated, the process may further include the step of (c) cooling the mixture formed in step (b) to room temperature.

[0086] Extraframework metal-containing aluminosilicate zeolites The extraframework metal-containing aluminosilicate zeolite obtained / obtainable by the above-mentioned process may have the composition described below.

[0087] Metal Ions vs. Metal Oxides The extraframework metal-containing aluminosilicate zeolite obtained / obtainable by the above-mentioned process may have a weight ratio of exchanged metal to metal oxide of ≧1, ≧2, ≧3, ≧4, ≧5, ≧6, ≧7, ≧8, ≧8.5, or ≧9, measured after calcining the aluminosilicate zeolite at 450° C. in air for 1 hour.

[0088] Metal weight percent The target loading of metal in the extraframework metal-containing aluminosilicate zeolite obtained / obtainable by the above process, calculated as the oxide of the metal, can be ≦10 wt%, ≦9 wt%, ≦8 wt%, ≦7 wt%, ≦6 wt%, ≦5 wt%, ≦4 wt%, or ≦3 wt%, depending on the metal and the aluminosilicate zeolite. The oxide of the metal can be MO, MO, or M2O, depending on the metal. x O y For example, if the metal is copper, the oxide of the metal is CuO. If the metal is iron, the oxide of the metal is Fe2O3. One skilled in the art will recognize that the target loading will depend on the aluminosilicate zeolite, the metal, and the intended use of the extra-framework metal-containing aluminosilicate zeolite. For example, metal-containing aluminosilicate zeolite can be used to extract NO x When treating exhaust gas containing a mixture of NO and NO, the target loading of metals on the aluminosilicate zeolite is x Different metal loadings can be selected to target the reduction of NO and N2O, so that NO xand may vary depending on the concentration of N2O.

[0089] Free Metals In addition to the metals exchanged to increase the concentration of metals associated with the exchange sites in the structure of the aluminosilicate zeolite, non-exchanged metals, so-called free metals, generally in the form of metal oxides or hydroxides, may be present on the surface of the aluminosilicate zeolite. In some embodiments of the invention, no free metals are present on the aluminosilicate zeolite.

[0090] Metal / Al The atomic ratio of metal to aluminum in the metal-containing aluminosilicate zeolite obtained / obtainable by the above process may be from about 0.05 to 1.4, preferably from about 0.25 to about 0.7.

[0091] The extraframework metal-containing aluminosilicate zeolites may be dried and / or treated and used as known in compositions and processes known for use with extraframework metal-containing aluminosilicates.

[0092] The above process can eliminate many of the post-treatment processes required when conventional ion exchange methods are used. After the extra-framework metal-containing aluminosilicate zeolite is formed, the aluminosilicate zeolite can be treated to obtain a purified aluminosilicate zeolite, preferably in solid form, using methods known to those skilled in the art. Preferably, the product mixture B containing the aluminosilicate zeolite can be used directly, without isolation or purification, to form a washcoat that can be applied to a substrate used to purify exhaust from an engine. There is no need to separate the extra-framework metal-containing aluminosilicate zeolite from the mother liquor resulting from the incorporation of the metal.

[0093] 2. Formation of a washcoat comprising product mixture B, which comprises an extraframework metal-containing aluminosilicate zeolite The process for preparing a washcoat comprising an extraframework metal-containing aluminosilicate zeolite includes the steps of: (a) providing a product mixture B comprising the extraframework metal-containing aluminosilicate zeolite; (b) combining the product mixture B with a binder, a rheology modifier, or a mixture of a binder and a rheology modifier to form a washcoat mixture C, i.e., a washcoat.

[0094] Washcoat mixture C includes product mixture B, which includes the extraframework metal-containing aluminosilicate zeolite, and one or more of a binder and a rheology control agent. Three different processes using the same materials can be used to form the washcoat. In the first process, the binder and the extraframework metal-containing aluminosilicate zeolite are combined and then the rheology modifier is added. In the second process, the rheology modifier and the extraframework metal-containing aluminosilicate zeolite are combined and then the binder is added. In the third process, the binder and rheology modifier are combined with the extraframework metal-containing aluminosilicate zeolite, and the binder and rheology modifier can be added simultaneously as a mixture or as two separate materials.

[0095] In each of these processes, when the two materials are combined, they can be combined in either order. For example, Product Mixture B can be combined with the binder mixture / solution by adding Product Mixture B to the binder mixture / solution or by adding the binder mixture / solution to Product Mixture B. The binder can be added as a powder or an aqueous slurry.

[0096] Binder Binders, also known as binding agents, are materials used to hold or attract other materials in a washcoat together and to the substrate to which it is applied.

[0097] The binder may include alumina, aluminum hydroxide, TiO2, SiO2, ZrO2, CeZrO2, SnO2, aluminophosphates, non-zeolitic aluminosilicates, silica-alumina, clays, or mixtures thereof.

[0098] The binder can be added in the form of a powder or in a slurry to the mixture containing the extraframework metal-containing aluminosilicate zeolite, i.e., Product Mixture B, or to the mixture containing Product Mixture B and the rheology modifier, to form Washcoat Mixture C, i.e., the washcoat.

[0099] The binder may be added to the washcoat mixture C in an amount of 1 to 20% of the total solids, preferably 1 to 15% of the total solids, and more preferably 1 to 10% of the total solids.

[0100] The binder may be added to product mixture B, ie, the reaction mixture, in an amount of 1 to 10% by weight, preferably 1 to 5% by weight.

[0101] Rheology Modifiers Rheology modifiers may include polysaccharides, starches, celluloses, alginates, celluloses (i.e., cellulosic materials), carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, methyl hydroxyethyl cellulose, methyl hydroxypropyl cellulose, and ethyl hydroxyethyl cellulose, carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, methyl hydroxyethyl cellulose, methyl hydroxypropyl cellulose, and ethyl hydroxyethyl cellulose, and mixtures thereof.

[0102] The rheology modifier may include clays such as laponite, kaolin, bentonite, or organoclays.

[0103] The rheology modifier may comprise at least one polysaccharide selected from the group consisting of galactomannan gum, xanthan gum, curdlan, schizophyllan, scleroglucan, deutan gum, welan gum, and mixtures of any two or more thereof. In embodiments where the washcoat requires low pH and high temperature stability, the rheology modifier preferably comprises scleroglucan and / or schizophyllan, with scleroglucan being particularly preferred.

[0104] Polysaccharide rheology modifiers may be or may be derived from starch, cellulose, or alginate, but these rheology modifiers do not share all of the properties of scleroglucan, welan gum, and deutan gum; for example, hydroxyethylcellulose may degrade when heated even at neutral or basic pH.

[0105] The cellulosic rheology modifier may be selected from the group consisting of carboxymethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, methyl cellulose, methylhydroxyethyl cellulose, methylhydroxypropyl cellulose, and ethylhydroxyethyl cellulose.

[0106] The polysaccharide rheology modifier may be an associative rheology modifier, examples of which include cellulosic materials such as hydrophobically modified hydroxyethyl cellulose or hydrophobically modified ethyl hydroxyethyl cellulose.

[0107] According to the present invention, it is possible to use a single rheology modifier as defined herein or a mixture or any two or more thereof. For example, in one embodiment, at least one rheology modifier may be a mixture of guar gum and xanthan gum.

[0108] A rheology control agent, either in powder form or as a slurry with water, can be added to Product Mixture B or a mixture containing Product Mixture B and a binder to form Washcoat Mixture C.

[0109] The rheology modifier may be added in an amount of 0.05 to 10% of the total solids, preferably 0.05 to 5% of the total solids, and more preferably 0.05 to 3% of the total solids.

[0110] The rheology modifier may be added in an amount of 0.1 to 10% by weight, preferably 0.1 to 5% by weight, of the product mixture B, which contains the extraframework metal-containing aluminosilicate zeolite.

[0111] Process for forming washcoat mixture C Washcoat mixture C comprises a mixture of (a) product mixture B comprising an extraframework metal-containing aluminosilicate zeolite, and (b) one or more of a binder and a rheology control agent.

[0112] When washcoat mixture C includes (i) product mixture B and (ii) a binder or rheology modifier, the binder or rheology modifier can be added directly to product mixture B, or product mixture B can be added directly to the binder or rheology modifier. Preferably, the binder or rheology modifier is present as a solution, slurry, or suspension.

[0113] When washcoat mixture C includes (i) product mixture B and (ii) a binder and a rheology modifier, three different processes using the same materials can be used to form the washcoat. In the first process, the binder is combined with product mixture B and then the rheology modifier is added. In the second process, the rheology modifier is combined with product mixture B and then the binder is added. In the third process, the binder and the rheology modifier are combined with product mixture B and the binder and the rheology modifier can be added simultaneously as a mixture or as two separate materials. In each of these processes, when two materials are combined, they can be combined in either order. For example, product mixture B can be combined with the binder mixture / solution by adding product mixture B to the binder mixture / solution or by adding the binder mixture / solution to product mixture B. The binder or rheology modifier can be added to product mixture B as a solution, slurry, or suspension. Alternatively, product mixture B can be added to a solution, slurry, or suspension of the binder or rheology modifier. These processes provide the flexibility needed by those skilled in the art.

[0114] In each of these three processes, the extra-framework metal-containing aluminosilicate zeolite is provided as cooled or unheated product mixture B, i.e., the product mixture obtained from the reaction, and when the mixture formed after the reaction is used directly in creating a washcoat, the metal from the metal-containing compound or free metal can be incorporated into the extra-framework sites in the aluminosilicate zeolite. Alternatively, the product mixture B formed after the reaction to incorporate the metal from the metal-containing compound or free metal into the extra-framework sites in the aluminosilicate zeolite can be treated to vary the concentration of the extra-framework metal-containing aluminosilicate zeolite in the mixture by varying the amount of water in the mixture. Generally, varying the amount of water is done to obtain a solid material or a more concentrated solution.

[0115] In each of these three processes, the pH of one or more of the solutions, slurries or suspensions containing the extra-framework metal-containing aluminosilicate zeolite, the binder, and the rheology modifier can be adjusted by the addition of a base. The base is an inorganic base, preferably a metal hydroxide, or an organic base, preferably an alkyl ammonia hydroxide, the alkyl ammonia hydroxide containing 4 to 16 carbon atoms. Preferably, the base is an alkyl ammonium hydroxide. The allyl ammonium hydroxide can be at least one of tetramethyl ammonium hydroxide (TMAOH), tetraethyl ammonium hydroxide (TEAOH), tetrapropyl ammonium hydroxide (TPAOH), and tetrabutyl ammonium hydroxide (TBAOH). Unlike steps a) and b) involved in the formation of the extra-framework metal-containing aluminosilicate zeolite, the base can include ammonia or ammonium ions. In one embodiment, the washcoat mixture C does not include ammonia or ammonium ions.

[0116] The process may further include adjusting the pH of the washcoat mixture C by adding a base. The amount of base added may be based on the amount of metal in the solution. - The concentration of can be higher than the concentration of free metal in solution, but the ratio of added OH-:free metal should be 2:1 or less. The base can be added to one or more of product mixture B, the binder, the rheology modifier, or a combination of two or more thereof. The base can be added after or at the same time as the addition of the binder or rheology modifier. When the binder and rheology modifier are added in separate input streams, the base can be added in either these input streams or in a separate input stream.

[0117] If a continuous process is used to form Product Mixture B, i.e., the reaction mixture, Product Mixture B can be combined with one or more of a binder and a rheology control agent. This can be done in either a batch or continuous process using mixing techniques known in the art.

[0118] The washcoat comprising or consisting essentially of the product mixture B and one or more of the binder and rheology modifier can be applied to a substrate using procedures well known to those skilled in the art. Preferably, the method used to apply the washcoat to the substrate is selected from the methods described in WO 9947260, WO 2011080525, or WO 2014195685, which are incorporated by reference.

[0119] The substrate, ceramic or metal monolith, may be a low or high porosity filter. The substrate may be a low or high porosity flow-through or wall-flow filter. Preferably, the filter is a wall-flow filter. Preferably, the filter has high porosity. The term "highly porous substrate" refers to a substrate having a porosity of about 40 to about 80%. A highly porous substrate may preferably have a porosity of at least about 45%, more preferably at least about 50%. A highly porous substrate may preferably have a porosity of less than about 75%, more preferably less than about 70%. The term porosity as used herein refers to the total porosity, preferably as measured by mercury porosimetry. Porosity is measured on an uncoated substrate.

[0120] The method may further include the step of drying and baking the substrate including the washcoat comprising product mixture B.

[0121] Calcination of the washcoated substrate can be carried out at temperatures ranging up to about 850° C. Calcination can be carried out stepwise at successive temperatures. The term “stepwise at successive temperatures” means that the washcoated substrate to be calcined is heated to a particular temperature, held at this temperature for a particular time, and heated from this temperature to at least one further temperature and held at that temperature for a particular time. By way of example, stepwise calcination is described in WO 2009 / 141324 (also published as U.S. Pat. No. 8,715,618), which is incorporated by reference.

[0122] Calcination can be under the influence of any suitable atmosphere, such as air, oxygen-depleted rarefied air, oxygen, nitrogen, water vapor, synthetic air, carbon dioxide, etc. Preferably, calcination is carried out under air. Calcination can be carried out in a dual regime, i.e. a regime involving a first calcination in an oxygen-reduced or oxygen-free atmosphere, and a second regime involving a second calcination in air, an oxygen-enriched or pure oxygen atmosphere. The humidity of the atmosphere can be controlled.

[0123] One of the major advantages of using the process described herein is the reduction in energy use, which results from the need for only one calcination on the washcoated substrate. Other methods currently in use require at least two calcinations, one to calcinate the metal-containing aluminosilicate zeolite and one to calcinate the washcoated support. These energy savings can be significant, especially considering the temperatures involved and the length of time the materials are calcined.

[0124] Other energy savings are found by being able to use the extra-framework metal-containing aluminosilicate zeolite directly in a washcoat instead of having to wash the metal-containing aluminosilicate zeolite when using conventional ion exchange methods. In addition, when using the methods described herein, the energy required to isolate the metal-containing aluminosilicate zeolite with currently used methods is not required.

[0125] Product by Process The present invention also relates to an extraframework metal-containing aluminosilicate zeolite obtainable or obtained by the process described above.

[0126] The following examples further illustrate the processes and materials of the present invention. EXAMPLES

[0127] The applicants report that H + It has been discovered that the use of an aluminosilicate zeolite in the NH4 form allows for a single step extra-framework metal exchange that results in higher metal loadings than the use of an aluminosilicate zeolite in the NH4 form, as shown in Example 1 below.

[0128] Example 1 Copper was dissolved in commercially available NH4 + Replace with CHA type, NH4 + The CHA type was treated with acid to produce H + Converted to CHA type and commercially available H + A sample of type CHA was evaluated by copper uptake from a copper acetate solution at 65° C. to give a copper zeolite with 2.4 wt % copper. The solids content was about 38%.

[0129] The same method as above was used, except that the initial concentration of copper in the solution was 3.3%.

[0130] [Table 1] The SAR values ​​in the above samples were determined before calcination and before the subsequent ion exchange. + When the H type was used, the Cu uptake rate decreased slightly (2-3%). When the ammonia type was used, the Cu uptake rate increased slightly (5%). + The NH4 type gave more consistent results than the NH4 type.

[0131] Example 2 - Cu Salt vs. Cu Salt Mixture Copper was added to the SAR22 using a single copper salt or a blend of copper salts. + The copper salt content was measured by the percentage of total exchangeable copper metal. Copper acetate was used as the primary copper source, and was blended with copper carbonate or copper hydroxide as the secondary source. + The CHA and Cu salts were added to deionized water and the system was heated with mixing to 65° C. The reaction mixture was held at 65° C. for 5 hours, at which point it was cooled to room temperature and a sample was taken for analysis.

[0132] The table below shows the copper uptake of copper-aluminosilicate zeolites produced by the above procedure using various copper salt blends. Both copper carbonate and copper hydroxide showed improved copper uptake with the addition of copper acetate over copper acetate alone.

[0133] [Table 2]

[0134] Example 3 As in Example 2, except that AEI with an SAR of 20 and 3.75% copper was used instead of CHA, the temperature was 70° C., and the percentage of copper from the copper hydroxide varied from 0 to 66.7%.

[0135] The table below shows the copper absorption rate for various percentages of copper hydroxide blended with copper acetate. As the percentage of copper hydroxide increases, even beyond the 50:50 ratio, copper absorption improves over copper acetate alone.

[0136] [Table 3]

[0137] Example 4 Using a single manganese salt, different amounts of manganese were added to H at SAR10. +Exchange of the solids to type AFX was investigated at 50 and 80° C. The solids were added to deionized water and the system was heated to 80° C. with mixing. The temperature was held for 2 hours at which point it was cooled to room temperature and a sample was taken for analysis.

[0138] The table below shows the absorption rate of manganese at different temperature and weight percent combinations. When the metal is manganese, the reaction temperature is important because higher temperatures improve the absorption rate of manganese. Excess manganese in solution reduces the absorption rate compared to lower weight percents.

[0139] [Table 4]

[0140] Example 5 Samples of CuCHA with Cu loadings of 2.4% Cu (low loading) and 3.3% Cu (high loading). The samples were aged under the following conditions tested to determine the NOx conversion resulting from using these samples at various temperatures. Before aging Medium: 750℃ / 80h / 10%H2O Severe: 900℃ / 4h / 4.5%H2O Mild: 620℃ / 100h / 10%H2O

[0141] When evaluated before aging (not shown), the NOx conversion based on the low loading sample at 200°C was 50,000 h -1 The NOx conversion was higher than 90% at a space velocity of 1000 C and the NH3 to NOx ratio was 1, suggesting adequate Cu exchange for the SCR reaction. After mild (620 C / 100 h / 10% H2O, Fig. 1) and moderate (750 C / 80 h / 10% H2O, Fig. 2) hydrothermal aging, the steady-state NOx conversion using the low loading sample was similar to the performance of the high loading sample. However, the N2O formation based on the low loading sample was higher than at 350 C. Following severe hydrothermal aging (900 C / 4 h / 4.5% H2O, Fig. 3), the low loading catalyst showed significant deactivation relative to the high loading sample.

Claims

1. 1. A process for preparing an extraframework metal-containing aluminosilicate zeolite comprising the steps of: (a)(i)H + forming a reaction mixture A comprising an aqueous slurry of an aluminosilicate zeolite of type A; and (ii) a metal-containing compound or free metal, said mixture being free of ammonia, ammonium hydroxide, or ammonium salts; (b) mixing the metal with the H in reaction mixture A; + and reacting said zeolite with a type aluminosilicate zeolite to form a product mixture B comprising said extraframework metal-containing aluminosilicate zeolite; The metal comprises one or more of copper, manganese, nickel, and palladium, and the metal is H + wherein said step of reacting with said aluminosilicate zeolite of type A after forming product mixture B is conducted in a single exchange and said extraframework metal-containing aluminosilicate zeolite is not separated from said mixture after said reaction.

2. 2. The process of claim 1, wherein the metal-containing compound or free metal of reaction mixture A further comprises an iron salt.

3. 3. The process of claim 1 or 2, wherein reaction mixture A has a pH, and the step of forming reaction mixture A further comprises adjusting the pH of reaction mixture A by addition of a base.

4. 4. The process of claim 3, wherein the base is an inorganic base, preferably a metal hydroxide, or an organic base, preferably an alkyl ammonia hydroxide, the alkyl ammonia hydroxide containing from 4 to 16 carbon atoms.

5. 5. The process of any one of claims 1 to 4, wherein the process further comprises adjusting the pH of product mixture B by adding a base to increase the amount of extraframework metals present in the extraframework metal-containing aluminosilicate zeolite.

6. 6. The process according to any one of claims 1 to 5, wherein reaction mixture A comprises from 5% to 50% by weight of the extraframework metal-containing aluminosilicate zeolite, preferably from 10% to 45% by weight, more preferably from 15% to 40% by weight.

7. 7. The process of any one of claims 1 to 6, wherein the step of reacting the reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite comprises mixing the reaction mixture at ambient temperature or at a temperature requiring cooling.

8. 8. The process of any one of claims 1 to 7, wherein the step of reacting reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite comprises reacting reaction mixture A at a temperature of 10 to 30°C.

9. 7. The process according to any one of claims 1 to 6, wherein the step of reacting reaction mixture A to form the extraframework metal-containing aluminosilicate zeolite comprises heating reaction mixture A to a temperature of from 30°C to 90°C, preferably from 40°C to 85°C, more preferably from 55°C to 75°C.

10. 10. The process of any one of claims 1 to 9, wherein when the metal-containing compound or free metal comprises copper acetate, reaction mixture A is heated to between 40°C and 85°C, more preferably between 55°C and 75°C.

11. A process according to any one of claims 1 to 6 and 10, comprising (c) cooling the mixture formed in step (b) to room temperature.

12. 12. The process of any one of claims 1 to 11, wherein the aluminosilicate zeolite is treated prior to step a, and the treatment changes one or more of the particle size of the aluminosilicate zeolite, the particle size distribution of the aluminosilicate zeolite, the acidity of the aluminosilicate zeolite, or the amount of dealumination.

13. 1. A process for preparing a washcoat comprising an extraframework metal-containing aluminosilicate zeolite, comprising: (a) providing a product mixture B comprising the extraframework metal-containing aluminosilicate zeolite; (b) combining the product mixture B with a binder, a rheology modifier, or a mixture of a binder and a rheology modifier to form a washcoat mixture C.

14. 14. The process of claim 13, wherein washcoat mixture C has a pH, the process further comprising adjusting the pH of washcoat mixture C by adding a base.

15. 15. The process of claim 14, wherein the step of adjusting the pH of washcoat mixture C occurs after or simultaneously with the addition of the binder, the rheology modifier, or a combination of the binder and the rheology modifier.

16. A process according to any one of claims 13 to 15, wherein the binder is added as a powder or a slurry to product mixture B comprising the extraframework metal-containing aluminosilicate zeolite.

17. The process according to any one of claims 13 to 16, wherein the binder is added in an amount of 1 to 20% of the total solids in washcoat mixture C, preferably 1 to 15% of the total solids, more preferably 1 to 10% of the total solids.

18. The process according to any one of claims 13 to 17, wherein the binder is added in an amount of 1 to 10 wt.%, preferably 1 to 5 wt.%, of the total weight of product mixture B.

19. The process according to any one of claims 13 to 18, wherein the rheology modifier is added in an amount of 1 to 20% of total solids in washcoat mixture C, preferably 1 to 15% of total solids, more preferably 1 to 10% of total solids.

20. The process according to any one of claims 13 to 19, wherein the rheology modifier is added in an amount of 1 to 10% by weight, preferably 1 to 5% by weight of product mixture B.

21. 21. The process according to any one of claims 14 to 20, wherein the base is an inorganic base, preferably a metal hydroxide, or an organic base, preferably an alkyl ammonia hydroxide, the alkyl ammonia hydroxide comprising from 4 to 16 carbon atoms.

22. The process of any one of claims 14 to 21, wherein the base is added in an amount such that the concentration of OH- in washcoat mixture C is greater than the concentration of the metal in washcoat mixture C.

23. The process of any one of claims 14 to 22, further comprising applying the washcoat mixture C onto a substrate to form a coated substrate.

Citation Information

Patent Citations

  • Product for defending and feeding plants and respective preparation method and use

    EP3238541A1

  • Hydrogen peroxide decomposing catalyst and method for disinfecting contact lens using the same

    JP1991275063A

  • Zeolite carrying divalent copper ions at a specific ratio, its manufacturing method and catalyst composition containing the same

    JP2020513305A

  • Catalyst for purifying exhaust gas containing organic nitrogen compound and method for purifying such exhaust gas

    WO2006006702A1

  • Agent for detoxifying discharge gas containing volatile inorganic hydride and method of detoxifying discharge gas containing volatile inorganic hydride

    WO2010109671A1